Reduction of embodied CO2 emissions from conventional single storey house in malaysia by recycled materials using building information modeling (BIM) - Shafiq, N. (American-Eurasian Network for Scientific Information, 2015)
The materials are the basic elements in any type of construction activity. The construction sector consumes a handsome amount of construction materials while completing any construction project and ultimately not only depleting the natural resources but also increasing the content contribution of CO2 from construction sector. In order to save the environment for our future generations, it is necessary that such alternate materials, which are environment friendly and also cost effective, shall be adopted in the construction sector. Recycled materials are one of the choices that can be adopted in this regard. Therefore, in order to access the magnitude, it is necessary to study the effect of embodied CO2 emissions from the materials, which are used in conventional housing construction Malaysia. This study focuses on the comparative analysis of embodied CO2 emission from the conventional construction materials and proposed recycled materials used in construction of a typical low cost house commonly adopted in Malaysia. The virtual model of selected single storey low cost was developed using Building Information Modeling (BIM) concept. The results highlighted that with incorporation of proposed recycled materials, a reduction of almost 24 of embodied CO2 emission can be achieved. The overall contribution of single storey house was observed to be reduced from 30 kg- CO2 /sq. ft to 22.65 kg- CO2/sq. ft. Â© 2015 AENSI Publisher All rights reserved.